Self-Management as a Determinant of Quality of Life among Type 2 Diabetes Mellitus Patients - Mustopa Alamsah, Saepul (Cindoku : Jurnal Keperawatan dan Ilmu Kesehatan, 2025)
Type 2 Diabetes Mellitus (T2DM) is a chronic disease that requires continuous self-care to prevent complications and maintain quality of life. Many patients in rural healthcare settings struggle with self-management, which may affect their overall well-being. This study aimed to analyze the relationship between self-management and quality of life among T2DM patients in Minajaya Ward, Jampangkulon Regional Hospital. A descriptive correlational method with a cross-sectional approach was used, involving 64 T2DM patients selected through simple random sampling. Data were collected using a self-administered questionnaire that measured self-management behaviors and perceived quality of life, and analyzed using chi-square statistical tests. The majority of respondents were over 35 years old, with low levels of education and a high proportion of housewives or unemployed individuals. Most respondents (56.3%) demonstrated poor self-management, while only 20.3% reported a good quality of life. The analysis showed a statistically significant relationship between self-management and quality of life (p-value = 0.000). Patients with better self-management consistently reported higher quality of life, suggesting that personal responsibility and consistent self-care behaviors are critical in managing T2DM. The study concludes that self-management plays a key role in determining the quality of life for T2DM patients and highlights the importance of educational and family-based interventions to improve diabetes care, especially in rural and low-literacy populations.